2022
DOI: 10.1161/strokeaha.121.037147
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Cerebral Aneurysms and Subarachnoid Hemorrhage

Abstract: Sex differences in cerebral aneurysm occurrence and characteristics have been well described. Although sex differences in outcomes following ischemic stroke have been identified, the effect of sex on outcomes following hemorrhagic stroke, and in particular, aneurysm treatment has been less studied. We describe the current state of knowledge regarding the impact of sex on treatment and outcomes of cerebral aneurysms. Although prior studies suggest that aneurysm prevalence and progression may be related to sex, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
39
3
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 119 publications
6
39
3
3
Order By: Relevance
“…In addition, we found that the location of aneurysms and irregular shape of IA were also associated with RIA, which was consistent with previous studies ( Greving et al, 2014 ; Fuentes et al, 2022 ; Wang et al, 2022 ). Future studies with larger sample sizes are needed to assess other associated factors.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In addition, we found that the location of aneurysms and irregular shape of IA were also associated with RIA, which was consistent with previous studies ( Greving et al, 2014 ; Fuentes et al, 2022 ; Wang et al, 2022 ). Future studies with larger sample sizes are needed to assess other associated factors.…”
Section: Discussionsupporting
confidence: 93%
“…These results suggest that Hcy levels may be related to the rupture of IA. Many risk factors have been reported to be associated with the rupture of IA, such as female sex, smoking, aneurysm location, aneurysm size, number of aneurysms, and a family history of SAH (Wiebers et al, 2003;Greving et al, 2014;Fuentes et al, 2022;Wang et al, 2022). However, these factors can only explain the risk of rupture of aneurysms to some extent (Kleinloog et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These were selected during consensus meetings of the study steering committee as those demonstrated to have potential associations with SAH outcome. [25][26][27] The primary outcome was dependency or death (mRS 3-6). The prespecified covariables were age, sex, modified Fisher grade, WFNS grade, aneurysm location and whether complications including vasospasm, ventriculitis or hydrocephalus occurred during admission up to 21 days, discharge or death.…”
Section: Discussionmentioning
confidence: 99%
“…To analyse associations of hyponatraemia with outcome, we used multiple logistic regression fit by maximum likelihood estimation, adjusting for prespecified covariates. These were selected during consensus meetings of the study steering committee as those demonstrated to have potential associations with SAH outcome 25–27. The primary outcome was dependency or death (mRS 3–6).…”
Section: Methodsmentioning
confidence: 99%